"A GOAT THAT IS ALREADY DEAD IS NO LONGER AFRAID OF KNIVES": Refugee Mobilizations and Politics of (Necessary) Interference in Hamburg. Issue 1 (11th April 2019) - Jørgensen, Martin Bak
Abstract : This article investigates the political activism undertaken by sub-Saharan West-African migrants residing in Hamburg. The article looks into political activism and resistance by exploring a politics of interference and emergence of new political subjectivities among African migrants. As stated by the refugees, they "did not survive the Nato war in Libya to die on the streets of Hamburg." The struggle works on different scales. It is based on a critique of the EU asylum and control system, of the Italian management of the "refugee problem", and of the local authorities of Hamburg. Furthermore, the article looks into how such political activism is diffused across local and national borders through local and transnational alliance-building.1